Auditory System Function and Disorders - Naz, Sadaf (IntechOpen, 2022)
Auditory System - Function and Disorders presents a concise description of the human auditory system and reviews the molecular biology of hearing loss with input from nine authors. It discusses the structure of the ear and associated malfunctions associated with hearing loss as well as auditory brainstem responses and their various applications. It summarizes various types of hearing loss and describes the roles of nonreceptor protein kinases and phosphatases, highlighting their importance to the function of the auditory system. Also discussed are new advancements in the treatment of hearing loss using implants and prosthetic devices. This book provides up-to-date information and is a useful resource for audiologists and geneticists, among others.